Maritime Networking: Bringing Internet to the Sea - Yau K.-L.A.; Syed A.R.; Hashim W.; Qadir J.; Wu C.; Hassan N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bandwidth; Ships; Surface waters; Wireless networks; Bandwidth-constrained; Dynamic network topology; Maritime networks; Research initiatives; Research interests; Variable bandwidths; Wireless broadband; Wireless multi-hop network; Ad hoc networks